ANALYSIS OF FACTORS THAT INFLUENCE THE ACCEPTANCE OF PBB-P2 TAX - Rahmawati, Novita; Soesilowati, Etty (Universitas Negeri Semarang, 2019)
The purpose of this study was to determine the effect of minimum wages, economic growth, and industry on unemployment in West Java. Industrial variables act as moderator variables. The method of data analysis in this study uses Multiple Regression. The type of data used is secondary data obtained from Badan Pusat Statistik (BPS) in 2013-2015 with 26 districts / cities in West Java. The results showed that the minimum wage had a positive and significant effect, economic growth had a positive but not significant effect, and the industry had a positive and significant effect. Moderating variables make the influence of minimum wages and economic growth have a negative and significant effect. The addition of moderation variables is proven to strengthen the influence of independent variables on the dependent variable. Suggestion: 1) the government must continue to regulate appropriate regulations so that an increase in the number of industries can be accompanied by an increase in employment opportunities. Economic growth will be better if it is able to provide employment opportunities; 2) Increasing number of industries is better when accompanied by increased employment opportunities. The community is encouraged to improve their skills to meet the criteria needed by the industry. Tujuan dari penelitian ini adalah untuk mengetahui pengaruh upah minimum, pertumbuhan ekonomi, dan industri terhadap pengangguran di Jawa Barat. Variabel industri bertindak sebagai variabel moderator. Metode analisis data dalam penelitian ini menggunakan Regresi Berganda. Jenis data yang digunakan adalah data sekunder yang diperoleh dari Badan Pusat Statistik (BPS) pada 2013-2015 dengan 26 kabupaten / kota di Jawa Barat. Hasil penelitian menunjukkan bahwa upah minimum memiliki efek positif dan signifikan, pertumbuhan ekonomi memiliki efek positif tetapi tidak signifikan, dan industri memiliki efek positif dan signifikan. Variabel moderat membuat pengaruh upah minimum dan pertumbuhan ekonomi berpengaruh negatif dan signifikan. Penambahan variabel moderasi terbukti memperkuat pengaruh variabel independen terhadap variabel dependen. Saran: 1) pemerintah harus terus mengatur peraturan yang tepat sehingga peningkatan jumlah industri dapat disertai dengan peningkatan kesempatan kerja. Pertumbuhan ekonomi akan lebih baik jika mampu memberikan kesempatan kerja; 2) Meningkatnya jumlah industri lebih baik jika disertai dengan peningkatan kesempatan kerja. Masyarakat didorong untuk meningkatkan keterampilan mereka untuk memenuhi kriteria yang dibutuhkan oleh industri.